Temporal and Spatial Pattern of Holcoglossum Schltr. (Orchidaceae), an East Asian Endemic Genus, Based on Nuclear and Chloroplast Genes - Zhao, Jiahong; Zhou, Peng; Li, Xiaoqian; Zhang, Liguo; Jin, Xiaohua; Xiang, Xiaoguo (Frontiers in Ecology and Evolution, 2020)
East Asia is one of the plant diversity and endemism centers in the world, and the temporal and spatial patterns and processes of vascular plants attracted ecologists’ and biogeographers’ attention. However, the biogeographic patterns of endemic epiphytic plants in East Asia are still unclear. Here, we investigated the historical biogeography of an East Asian endemic epiphytic genus Holcoglossum Schltr. (Orchidaceae). Using DNA sequences of eleven chloroplast genes and one nuclear gene, we reconstructed a robust phylogenetic framework for Holcoglossum and used a relaxed-clock method to estimate divergent times for the genus. We inferred the ancestral range of lineages under the statistical dispersal-extinction cladogenesis (S-DEC) and statistical dispersal-vicariance analysis (S-DIVA), respectively. Biogeographical analysis suggested that the most recent common ancestor of Holcoglossum occurred in the Palaeotropical region in the late Miocene (6.33 Ma). Four dispersal events were inferred to explain the Holcoglossum expansion to Sino-Himalayan, Sino-Japanese, and Taiwan regions from the latest Miocene to Quaternary. The episodes of these events were associated with intensification of East Asian monsoon around 3.6–2.6 Ma and global cooling since the latest Pliocene. The disjunct distribution between mainland China and Taiwan was attributed by the sea-level fluctuations and climate changes during the late Pliocene. This study shed light on the biogeographic processes of endemic epiphytic plants in East Asia.